2021
DOI: 10.1080/21505594.2020.1867468
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of carbapenem resistance and hypervirulence in a highly-transmissible ST11 clone of K. pneumoniae: An epidemiological, genomic and functional study

Abstract: Co-occurrence of hypervirulence and KPC-2 carbapenem resistant phenotypes in a highly-transmissible ST11 clone of Klebsiella pneumoniae has elicited deep concerns from public health stand point. To address this puzzle, we conducted a large-scale epidemiological, clinical and genomic study of K. pneumonia ST11 clones with both hypervirulence and carbapenem resistance in two tertiary hospitals in Zhejiang province. Most of the patients (15/23) were diagnosed with exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 52 publications
2
36
1
Order By: Relevance
“…Hypervirulent (Hv) Klebsiella pneumoniae (Kp) is a notorious pathogen causing a wide spectrum of infections in immunocompetent patients as well as immunosuppressed patients ( Shon et al, 2013 ). This pathotype is being increasingly reported in the last decade among community- and healthcare-associated infections and has acquired antimicrobial resistance, unlike its former counterpart ( Zhan et al, 2017 ; Hao et al, 2020 ; Li et al, 2021 ). The virulence plasmid described earlier such as the pLVPK and pK2044 lacked genes coding for antimicrobial resistance and typically belonged to IncHI1B ( Chen et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypervirulent (Hv) Klebsiella pneumoniae (Kp) is a notorious pathogen causing a wide spectrum of infections in immunocompetent patients as well as immunosuppressed patients ( Shon et al, 2013 ). This pathotype is being increasingly reported in the last decade among community- and healthcare-associated infections and has acquired antimicrobial resistance, unlike its former counterpart ( Zhan et al, 2017 ; Hao et al, 2020 ; Li et al, 2021 ). The virulence plasmid described earlier such as the pLVPK and pK2044 lacked genes coding for antimicrobial resistance and typically belonged to IncHI1B ( Chen et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reports of fusion/mosaic plasmids that carry two replicons such as IncHI1B–IncFIB and IncFIIK–IncFIBK are emerging, which code for antimicrobial resistance determinants as well as virulence genes ( Lam et al, 2019 ; Turton et al, 2019 ). Furthermore, HvKp is no longer confined to selected clones but is reported among regional endemic clones such as ST11 in China and ST147 in Europe ( Turton et al, 2019 ; Li et al, 2021 ). Hence, the threat of these superbugs is increasing, and this pathotype is evolving at a tremendous pace.…”
Section: Introductionmentioning
confidence: 99%
“…K. pneumoniae is prominent in the WHO bacterial priority pathogen list and as such has been the subject of several phage studies. This is especially for well-established lineages of Klebsiella considered high-risk clones (e.g., ST11) because of high antimicrobial resistance rates and virulence 22,23 The 14 fully characterised bacteriophages in this study were of diverse sequence and morphology and were members of five different families (Figure 1). Viruses belonging to Autographiviridae had the best activity against our Klebsiella collection (Figure 3).…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with the increasing trend of CR-hvKP literature reports. Since the first description of CR-hvKP by Zhang et al in 2015, 10 more and more CR-hvKP literature has been reported, [17][18][19][20] mainly in the Asia-Pacific region, especially in China. CR-hvKP is a super bacterium with hypervirulence and multidrug resistance, which has great harm to people's health and high mortality rate.…”
Section: Discussionmentioning
confidence: 99%